Comparison trend of usage between Proton Pump Inhibitors and H2-Antagonist in Medical and Surgical Department at Hospital Raja Perempuan Zainab II for six months period of time within January until June 2008 - Suhaimi, Suhartini; Wan Azman, Wan Nurfarahiyah; Idris, Siti Nor Rohayah; Mohd Noor, Siti Safiah (2009)
Proton Pump Inhibitors (PPI) inhibits gastric acid secretion by blocking the hydrogen-potassium adenosine triphosphate enzyme system of gastric parietal cell. Proton pump inhibitors are effective short term treatments for gastric and duodenal ulcers. They are also used in combination with antibacterials for the eradication of H. pylori. Proton pump inhibitor can be used in the treatment of dyspepsia and GERD.